Negative capacitance gate-all-around PZT silicon nanowire with high-K/metal gate MFIS structure for low SS and high Ion/Ioff. (1st May 2023) - Kumar, Vivek; Maurya, Ravindra Kumar; Malvika,; Rawat, Gopal; Mummaneni, Kavicharan
Abstract: In the present work, a high- k dielectric hafnium dioxide and lead zirconate titanate (PZT) have been incorporated as a ferroelectric (FE) layer in the gate stack. The Ion /Ioff ratio obtained of the order of 10 13, and the subthreshold swing 49.7 mV dec −1 are the most captivating findings of the device which outshines earlier findings. There is a significant improvement in the on-state current ( I on ) and off-state current ( I off ). Furthermore, comparatively high value of transconductance ( g m ) and transconductance generation factor ( g m / I d ), due to the incorporation of 20 nm PZT NC FE layer, insinuates that the device could be used in low power applications. These enticing findings of the proposed PZT GAA-NCFET nanowire could pave the way for low power devices.